Flow interactions with an aquatic macrophyte: a field study using stereoscopic particle image velocimetry. Issue 2 (3rd July 2019) - Biggs, H. J.; Nikora, V. I.; Gibbins, C. N.; Cameron, S. M.; Papadopoulos, K.; Stewart, M.; Fraser, S.; Vettori, D.; Savio, M.; O'Hare, M. T.; Kucher, M.; Hicks, D. M.
Abstract: This paper reports the morphology of a natural patch of Ranunculus penicillatus and presents high-resolution measurements of flow velocities in its wake using a stereoscopic PIV field measurement system. The patch was 3.80 m long, 1.24 m wide and caused substantial changes to downstream mean velocities and turbulence. Vertical profiles of streamwise mean velocity were not logarithmic and flow was redirected under the positively buoyant canopy, enhancing vertical turbulent mixing in the wake and generating a large region where the velocity covariance u ′ w ′ ¯ was positive. Turbulent kinetic energy was enhanced downstream from the patch lateral shear layer, but not at the centre of the wake. Spectra downstream from the patch showed that turbulence was neither dominated by fine-scale nor large-scale structures, likely due to the low energy of the flow conditions and lack of a developed vortex street within the measurement domain. Sedimentation was observed at the upstream end of the patch, but not underneath the floating canopy. The methods and results of this work will be useful for planning other in situ studies. Also, the reported data on macrophyte geometry and biometrics will assist with the design of more realistic replicas for use in laboratory studies.